Implementasi Sistem Autentifikasi Terintegrasi Pada Domain Controller Dan Application Server Labkom STIKOM Surabaya - Putra, Diki Anggoro; Supriyanto, Antok; Jatmika, Kurniawan (Jurnal JSIKA, 2012)
When the practice process begins, practitioner are able to access the PDC-Labkom system. But, at the same time, one computer can be used by the other practices. Problems that come on the surface are one computer can be worn for multiple accounts when accessing domain controller and there is no login managemet recording to actuate the practician’s history. Single sign on is a technology that granted the user’s network for accessing rescources inside using one single account. They only need to authenticate once and then granted to access all the services on the network. For application services, the system is using web-service. Web-service is a bunch of logics application providing data and services for the application which used by it. From that existing problems, the system have been bulit using web-service and SSO method as an integrated authentification at domain controller and application server on the practice system Labkom Stikom Surabaya. This SSO is a technology using the user and the password taken from login domain. And it can handle multi account security on the practice process. Furthermore, Labkom are able to record practitioner’ histroy or mutli account for cheating history and login management safety. Keywords : Practicum, Login, Single Sign-On